The healing-promoting effect of saliva on skin burn is mediated by epidermal growth factor (EGF): role of the neutrophils - YEGEN, BERRAK (ELSEVIER SCI LTD, 2004)
Local skin trauma induces inflammatory responses resulting in local tissue and distant organ injury. EGF, a polypeptide hormone, mainly produced in saliva, is one of the major accelerators in wound healing. Wistar albino rats of both sexes received either bovine serum albumin or EGF (10 mug/kg) subcutaneously before a circular (18 mm diameter) partial thickness burn was induced. Afterwards, some rats were placed in separate cages to prevent licking, while the others were caged together to allow wound-licking. Treatments were continued for 5 more days and on the 5th day animals were decapitated. Histopathological analysis of skin damage and dermal myeloperoxidase (MPO) activity, as an index for neutrophil activity, were evaluated. Oxidant injury to the liver and intestines was determined by measuring glutathione (GSH) and malondialdehyde (MDA) levels, as well as MPO activity. The results demonstrate that healing of the burn wound on the skin is accelerated by both wound-licking and EGF administration, which also attenuated tissue neutrophil accumulation, suggesting the role of neutrophils as the source of mediators involved in delayed epithelial regeneration. Moreover, local dermal burn results in oxidant injury to the liver, concomitant with significant elevations in hepatic and intestinal GSH levels. Exogenous administration of EGF at physiological doses had no effect on inflammatory responses of the distant organs, while allowing the rats to lick the wound reduced the oxidant injury to the liver. Since saliva or EGF enhances skin Wound healing, topical use of EGF-rich artificial saliva merits consideration for its use in burn patients. (C) 2004 Elsevier Ltd and ISBI. All rights reserved.
Keywords: epidermal growth factor; myeloperoxidase activity; oxidant injury; thermal trauma; FACTOR-ALPHA; THERMAL-INJURY; MICE; RAT; INFLAMMATION; ENHANCEMENT; RECEPTOR